The Wage Performance of Immigrant Women: Full-Time Jobs, Part-Time Jobs, and the Role of Selection - Christian Dustmann; Christoph M. Schmidt (Institute for the Study of Labor (IZA), 2000)
This paper contrasts labour participation behaviour and wages of native and immigrant women. Since the impact of family structure on labor supply differs between natives and immigrants, we explicitly distinguish between part-time and full-time jobs. The choice of jobs is accounted for by an ordered probit selection model with an incidental threshold, thus offering a flexible strategy to address selection issues in a segmented labour market. Our analysis is based on panel data, allowing us to control for correlated individual-specific effects in both selection- and wage equations. We conclude that migrant women receive lower wages than native women in the same labor market segment, and that this is mainly associated with their relatively low educational endowments. Their relatively high ability to combine full-time work and child rearing somewhat mitigates these disadvantages.
Keywords: J22; J61; J31; 330; Assimilation; segmented labour markets; discrete choice models; Frauenerwerbstätigkeit; Frauenarbeitslohn; Ethnische Gruppe; Migranten; Mikroökonometrie; Arbeitsmarktsegmentierung; Schätzung; Deutschland